Modal analysis of the coffee fruit-peduncle-branch system coffee fruit-peduncle-branch system - Wellington Washington Andrade de Melo, Júnior; Fábio Lúcio Santos; Francisco Scinocca (Smart Agricultural Technology, 2023)
The mechanized harvesting of coffee fruits is performed by machines that uses the mechanical vibrations principles and has been widely adopted due the operational cost reductions compared to manual way. Maturation stages, frequency and amplitude of vibration influence the fruits detachment during the mechanized harvesting by mechanical vibrations. In this context, the determination of the modal parameters of the coffee plant is essential, considering, the full and selective harvesting. Modal analysis can be performed experimentally by using a specific instrumentation and, from this technique, it is possible to determine the vibration modes, damping factors and natural frequencies of the system in order to identify its dynamical behavior, supporting in the design and set-up of harvesting machines. In this way, this study was developed with the objective of determining and evaluating the modal characteristics of the coffee fruit-peduncle-branch system, such as the natural frequency, ratio and damping coefficient, from impact modal analysis. Additionally, the influence of the maturation stage, branch configurations (with/without leaves and fruits) and plant position in relation to the modal parameters of the system were evaluated. For branches without leaves and with fruits in different stages of maturation, several scenarios were studied. The results obtained verify that branches with ripe fruits (25.51 Hz, 24.19 Hz and 16.00 Hz for upper, middle and lower position in the plant, respectively) generally showed higher mean natural frequencies than branches with unripe fruits (16.77 Hz, 15.30 Hz and 15.49 Hz for upper, middle and lower position in the plant, respectively). For the complete branches with leaves and fruits, no significant differences in the first natural frequency were found between the mean natural frequencies throughout the plant and for different maturation stages. This pattern was repeated for the second and third natural frequencies, except for the difference in the average natural frequency found for branches with ripe fruits in the middle third of the plant. This behavior may be an important finding for the adjustment of harvesting machines since there was no differentiation between the average values of the natural frequency throughout the plant.